The evaluation of idiopathic osteosclerosis on panoramic radiographs with an investigation of lesion's relationship with mandibular canal by using cross-sectional cone-beam computed tomography images - Melda Misirlioglu; Rana Nalcaci; Mehmet Zahit Adisen; Selmi Yilmaz (Wolters Kluwer Medknow Publications, 2013)
Objective: The aim of this study was to determine the prevalence of idiopathic osteosclerosis (IO) in a Turkish population on orthopantomographs with respect to age, sex, and lesion characteristics and investigate the lesion's relationship with mandibular canal with the aid of cross-sectional cone-beam computed tomography (CBCT) images. Materials and Methods: 8000 panoramic radiographs taken with two digital orthopantomograph devices over a 10-month period were evaluated. Each patient was assigned an identification number, and demographic information (age, sex), absence/presence of a lesion, and if present, lesion characteristics (localization, dental relationship, size, and shape) were recorded. Additionally, cross-sectional CBCT images of 30 patients with IO were examined in terms of relationship with mandibular canal. Results: 273 IO lesions were detected in 225 patients (130 females, 95 males; mean age: 33.1 years). The majority of lesions were observed in the mandibular premolar and molar areas. IO lesions occurred more frequently among middle-aged individuals and at higher rates among females (3.1%, n = 130) than males (2.8%, n = 95); however, differences by age and sex were not statistically significant (P > 0.05). Cross-sectional images revealed that 80% of the lesions were in contact with mandibular canal. None of the lesions showed any cortical expansion. Conclusions: This large-scale study found IO to have a low prevalence rate among a Turkish population. IO was observed to occur more frequently in females than in males and to be most common among individuals aged 20-29. CBCT results suggested a possible association between IO lesions and mandibular canal.